Day 1 Mon, November 23, 2015 2015
DOI: 10.2118/178467-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Cycling on Cement Sheath Integrity: Realistic Experimental Tests and Simulation of Resulting Leakages

Abstract: The cement sheath is one of the most important well barrier elements in the well, both during production and after abandonment. However, normal production operations which involve temperature variations in the well, such as steam injection, stimulations and shut-down periods, may damage the integrity of the cement sheath. Temperature increase and decrease, i.e. thermal cycling, cause the casing to expand and contract, which creates debonding and cracking of the cement sheath and thereby loss of zonal isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Submitting Equations (2) and (3) into Equation (1), the thermal radial displacement and thermal stresses for the combined system can be determined and the detailed derivative results are given below [12].…”
Section: Appendix a Cement Sheath Stress Induced By A Decrease Of Wementioning
confidence: 99%
See 1 more Smart Citation
“…Submitting Equations (2) and (3) into Equation (1), the thermal radial displacement and thermal stresses for the combined system can be determined and the detailed derivative results are given below [12].…”
Section: Appendix a Cement Sheath Stress Induced By A Decrease Of Wementioning
confidence: 99%
“…For maintaining gas well's long-term and safe production, mechanical integrity of cement sheath has been given more emphasis in recent years. Field experiences and laboratory studies have both proven that cement sheath is very likely to fail after downhole operations, such as pressure testing, hydraulic fracturing, acidizing, steam injection, and more [1][2][3]. The cement sheath fails mainly because of the loads from variations of wellbore temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In our group, we have recently developed an experimental characterization procedure where we use CT for 3D digital visualization of well cement in realistic annular geometries. With our dedicated and tailor-built cement sheath integrity experimental set-up [41,42], we have visualized microannuli and cracks in cement formed during thermal cycling [41,[43][44][45][46] and pressure cycling [42,[47][48][49], and we have also used the digital cracks and microannuli obtained from CT scans as imported leak path geometries in computational fluid flow simulations [45,[50][51][52]. Furthermore, we have also used CT to study cement-formation bonding [53][54][55][56], cement durability [57,58], and cement-mud interactions [59].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to ensure the wellbore maintains mechanical and hydraulic integrity during fracturing and long-term production, the open hole for geothermal wells is usually cemented with a steel casing. However, laboratory investigations and field practice have both shown that the cement sheath is likely to fail at some stage in downhole operations due to additional stresses within the cement sheath from variations of wellbore temperature and pressure [16][17][18]. For fracturing wells, wellbore temperature may suffer a very significant decrease (up to −70 • C) [19] because of high displacement and pump pressure during fracturing fluid injection, and the casing and cement sheath very likely fail in this case.…”
Section: Introductionmentioning
confidence: 99%